A review and update of the Health of the Nation Outcome Scales (HoNOS). (5th March 2018) - James, Mick; Painter, Jon; Buckingham, Bill; Stewart, Malcolm W.
Abstract : Aims and method: The Health of the Nation Outcome Scales (HoNOS) and its older adults' version (HoNOS 65+) have been used widely for 20 years, but their glossaries have not been revised to reflect clinicians' experiences or changes in service delivery. The Royal College of Psychiatrists convened an international advisory board, with UK, Australian and New Zealand expertise, to identify desirable amendments. The aim was to improve rater experience by removing ambiguity and inconsistency in the glossary rather than more radical revision. Results: Changes proposed to the HoNOS are reported. HoNOS 65+ changes will be reported separately. Based on the views and experience of the countries involved, a series of amendments were identified. Clinical implications: While effective clinician training remains critically important, these revisions aim to improve intra- and interrater reliability and improve validity. Next steps will depend on feedback from HoNOS users. Reliability and validity testing will depend on funding. Declaration of interest: None.